Antecedents of the Hanukkah Oil Story - Ron, Zvi (The review of rabbinic Judaism, 2015)
When the rabbis in the Babylonian Talmud (Shabbat 21b) recounted the miracle of the oil’s lasting for eight days as the etiology of the festival of Hanukkah, they were basing themselves on biblical antecedents, in which the dedication of the Temple/tabernacle was accompanied by the descent of heavenly fire. Although there is no trace of the legend of the oil in any source before the Talmud, an analogous story is found in 2 Maccabees 1 in relation to Nehemiah, whose dedication of the Second Temple was accomplished through the fire of the First Temple, which had in the meanwhile liquefied into naphtha and was kept in an empty cistern. Another story that adumbrates the same themes is the discovery of the lost scroll under Josiah, which leads to the purification and renewal of the Temple. In each case an object from the past survives catastrophe or the reign of bad kings to provide continuity. A final case is the narrative of the building of the Temple in Ezra 6, in which the discovery of a lost scroll in the Achaemenid summer palace authorizes the construction. The Talmudic Hanukkah story is thus seen as a midrash based on biblical precedents.